1998
DOI: 10.1161/01.str.29.12.2461
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hypothermia in the Treatment of Patients With Severe Middle Cerebral Artery Infarction

Abstract: Background and Purpose-Animal research and clinical studies in head trauma patients suggest that moderate hypothermia may improve outcome by attenuating the deleterious metabolic processes in neuronal injury. Clinical studies on moderate hypothermia in the treatment of acute ischemic stroke patients are still lacking. Methods-Moderate hypothermia was induced in 25 patients with severe ischemic stroke in the middle cerebral artery (MCA) territory for therapy of postischemic brain edema. Hypothermia was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
360
1
14

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 598 publications
(386 citation statements)
references
References 51 publications
11
360
1
14
Order By: Relevance
“…and traumatic brain injuries has been obtained (Marion et al, 1997;Clifton et al, 1993;Polderman et al, 2002;Schwab et al, 1998), more experimental data are required to answer major scientific questions regarding therapeutic hypothermia, including therapeutic window, level and duration of hypothermia, rewarming phase, and gender considerations.…”
Section: Figmentioning
confidence: 99%
“…and traumatic brain injuries has been obtained (Marion et al, 1997;Clifton et al, 1993;Polderman et al, 2002;Schwab et al, 1998), more experimental data are required to answer major scientific questions regarding therapeutic hypothermia, including therapeutic window, level and duration of hypothermia, rewarming phase, and gender considerations.…”
Section: Figmentioning
confidence: 99%
“…Other therapeutic strategies for stroke include hypothermia [20,65,81], antioxidants [7,13,14,64], blockade of excessive synaptic Zn 2+ release [75], antiapoptotic strategies [26,53], administration of growth factors [1,40], erythropoietin [67], recombinant human interleukin-1 receptor antagonist [47], statins [73], gene therapy [80,81] and approaches involving transfer of new cells, such as stem cells, and neuronal precursors cells [1,46,63].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Additionally, preliminary clinical findings suggested that moderate hypothermia may influence mortality in patients with malignant middle cerebral artery infarction. 7,8 Currently, hypothermia is being induced by surface cooling with the use of cooling blankets, alcohol applied to exposed skin, or ice bags to groin, axilla, and neck. This approach, however, requires intensive effort from the medical and nursing staff for induction as well as maintenance of the target temperature.…”
mentioning
confidence: 99%